2012
DOI: 10.1136/annrheumdis-2011-201189
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of immunoglobulin-producing cells in parotid salivary glands of patients with primary Sjögren's syndrome after B cell depletion therapy

Abstract: Rituximab treatment does not alter the characteristic features of increased clonal expansions seen in the parotid salivary glands of patients with pSS. The presence of clonally related immunoglobulin-producing cells before and after rituximab treatment strongly suggests that immunoglobulin-producing cells persist in salivary glands of patients with pSS despite B cell depletion. The presence of mixed isotype expression within groups of clonally related cells indicates local class switching in salivary glands of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
37
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 42 publications
(55 reference statements)
4
37
1
2
Order By: Relevance
“…However, there are reports of CD20 + plasma cells being present in tonsils even after RTX (19). We also observed more mutations in the Ig H chain V region (IGHV) genes obtained from salivary glands after RTX compared with their clonally related counterparts present before RTX (18). This is an indication that Ig-producing cells surviving after RTX continue to proliferate.…”
mentioning
confidence: 54%
See 2 more Smart Citations
“…However, there are reports of CD20 + plasma cells being present in tonsils even after RTX (19). We also observed more mutations in the Ig H chain V region (IGHV) genes obtained from salivary glands after RTX compared with their clonally related counterparts present before RTX (18). This is an indication that Ig-producing cells surviving after RTX continue to proliferate.…”
mentioning
confidence: 54%
“…Hence, we prudently maximized the use of these biopsies by conducting our study on a few tissue sections from each biopsy and not on whole biopsies. The rest of the sections were used for immunohistochemistry in our previous study (18).…”
Section: Cloning Sequencing and Analysis Of Ig Sequencesmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, plasma cells can persist in parotid glands of pSS patients despite B cell depletion therapy, since they lack expression of CD20 [30]. However, it is not known if absolute numbers of plasma cells in salivary glands are affected by rituximab and whether this is associated with response to treatment.…”
Section: Histological Markers Of B Cell Hyperactivitymentioning
confidence: 83%
“…However, the local persistence of clonally related Ig-producing B cells in SGs and PB has been reported despite RTX treatment, suggesting the lack of a full restoration of the B-cell repertoire to a pre-disease state. 29,30 Indeed, persistence of B-cell clones may explain the occurrence of relapses after treatment, possibly triggered by additional pathologic stimuli. In fact, it has been shown that B-cell depletion therapy is followed by an increase of serum BAFF levels, inversely correlated to the B-cell number after repopulation, and highlighting the role of BAFF in B-cell homeostasis both in health and B-cell diseases.…”
Section: Rituximab In Pss: Biological Effectsmentioning
confidence: 99%